Dose-response Relationship Between Donor Human Milk, Mother's Own Milk, Preterm Formula, and Neonatal Growth Outcomes. Issue 1 (July 2018) - Brownell, Elizabeth A.; Matson, Adam P.; Smith, Kelsey C.; Moore, James E.; Esposito, Patricia A.; Lussier, Mary M.; Lerer, Trudy J.; Hagadorn, James I.
ABSTRACT: Background: A dose-response relationship between proportions of donor human milk (DHM) intake and in-neonatal intensive care unit (in-NICU) growth rates, if any, remains poorly defined. Objective was to evaluate interrelationships between percentages of DHM, mother's own milk (MOM), and preterm formula (PF) intake and neonatal growth parameters at 36 weeks postmenstrual age or NICU discharge. Methods: Infants eligible for this single-center retrospective study were inborn at ⩽32 weeks gestation or ⩽1800 g, stayed in the NICU for ≥7 days, and received enteral nutrition consisting of human milk fortified with Enfamil human milk fortifier acidified liquid. Study exposures were defined as 10% increments in the total volumetric proportions of infant diet provided as MOM, DHM, or PF. Outcomes were growth parameters at 36 weeks postmenstrual age or NICU discharge. Multivariable linear regression modeled the adjusted additive effect of infant diet on individual growth parameters. Results: A total of 314 infants records were eligible for analysis. Using MOM as reference, the adjusted mean growth velocity for weight significantly decreased by 0.17 g · kg −1 · day −1 for every 10% increase in DHM intake, but did not vary with PF intake. The adjusted mean change in weight z score significantly decreased with increasing proportion of DHM intake but significantly improved with increasing PF intake. The adjusted mean head circumference velocity was significantly decreased by 0.01 cm/wk for every 10% increase in DHM intake, in reference to MOM, but did not vary with PF intake. Neither proportion of DHM nor PF intake was associated with length velocity. Conclusions: When DHM and MOM are fortified interchangeably, preterm infants receiving incremental amounts of DHM are at increased risk of postnatal growth restriction. The dose-response relationship between DHM, MOM, and PF and long-term growth and neurodevelopmental outcomes warrants further research.